Analisis Pengurangan Waste Proses Produksi pada PT SP Manufacturing - Simaremare, Erna; Elsya Paskaria Loyda Tarigan (SURYA TEKNIKA, 2024)
PT SP Manufacturing is a manufacturing company that operates in the field of wire harness production. When making wire harnesses at PT SP Manufacturing, waste still occurs. Waste in the production process is one of the biggest problems this company wants to solve. A defective product is a product that does not meet wire harness production standards so it cannot meet customer demand, and requires more space before rework is carried out, which causes inventory waste (Unnecessary Inventory). Reduced productivity and higher production costs are the result of this waste. The aim of this research is to use value stream mapping to identify waste in the production process and apply lean manufacturing techniques to reduce it. The results obtained are based on identification and analysis of existing problems as well as alternatives and improvements based on the formulation and objectives in the research. The largest waste in the wire harness production process of PT.SP Manufacturing is waste with a weight score of 60.89%, unknown inventory waste with a weight score of 39, 12%. The causal factors are workers who lack concentration, apply excess solder paste to the wire terminals, workers who pursue targets without paying attention to quality, resulting in defective products that require rework. The recommendations given to the company according to the fishbone diagram are proposed improvements to the wire harness production process to reduce defects and unnecessary inventory which refers to people, machines, methods and materials.